2018
DOI: 10.1002/sdtp.12333
|View full text |Cite
|
Sign up to set email alerts
|

50‐3: Formation of Source and Drain Regions in Top‐Gate Self‐Aligned Oxide Semiconductor Field‐Effect Transistor

Abstract: Formation of source and drain regions in a top-gate self-aligned field-effect transistor and its mechanism were examined. A stack structure of silicon nitride and an oxide semiconductor (OS) is effective, and hydrogen trapped in oxygen vacancies in the OS and the presence of metallic indium at the interface are important. Author KeywordsTGSA; OS FET; short channel length; formation method of S-D regions; CAAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In case of TFT backplane, Oxide TFTs have been used as OLED display backplanes, which are different from a-Si TFTs commonly used for LCDs. Its structure has been developed into a coplanar type with small and low parasitic capacitance to increase the pixel aperture ratio [4]. From a performance point of view, there were improvements in TFT characteristic and improvement in reliability characteristics [5].…”
Section: Introductionmentioning
confidence: 99%
“…In case of TFT backplane, Oxide TFTs have been used as OLED display backplanes, which are different from a-Si TFTs commonly used for LCDs. Its structure has been developed into a coplanar type with small and low parasitic capacitance to increase the pixel aperture ratio [4]. From a performance point of view, there were improvements in TFT characteristic and improvement in reliability characteristics [5].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group previously reported on back-channel-etched (BCE) and top-gate self-aligned (TGSA) field-effect transistors (FETs) with oxide semiconductor (OS) active layers [1][2][3][4][5][6]. OSbased FET (OSFET) technologies have recently been widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…The authors previously developed OS FETs with back-channeletched (BCE) and top-gate self-aligned (TGSA) structures [1][2][3][4][5][6]. BCE OS FETs can be fabricated using fewer masks than those required for TGSA OS FETs.…”
Section: Introductionmentioning
confidence: 99%